Pengembangan Sistem Pengelolaan Toko ATK Pak Eko berbasis Payment Gateway - Dimas Ivon Anggitama; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Pak Eko's ATK provides stationery and printing services that are needed by students. It makes the number of customer are numerous so efficiency is needed in transaction process so the services provided can be more optimal and it can reach out more customer. Therefore, an this system is needed to make transactions efficient and also to expand the reach of sales and product marketing. It easier for prospective buyers to view products and print service online without go to the store first and the payment process where the cashless method with payment gateway is more popular these days. Requirements analysis obtained 22 functional requirements along with 1 non functional requirement which compatibility. Process of system design and system implement are refers to functional requirements that have been defined. Implementation used Flutter and Firebase as data storage media. Unit testing produces a valid result on each path tested in 3 unit sample, integration testing produces a valid result in 1 test case, and validation testing produces valid result on 1 functional sample with 5 test scenario.